The role of technological pedagogical and content knowledge on career adaptability among teachers in Indonesia and Malaysia - Kusmaryani, Rosita Endang; Widyastuti, Tria; Nurhayati, Siti Rohmah; Hamzah, Hazalizah (International Journal of Public Health Science (IJPHS), 2025)
Since the COVID-19 pandemic, face-to-face learning has been transformed into online learning. This phenomenon was really challenging for teachers because they were not used to it. The adaptability of the teacher becomes an indispensable aspect to face the problem. The ability to integrate materials, pedagogy and technology or technological pedagogical and content knowledge (TPACK) supported the adaptability in implementing online learning. The purpose of this study was to investigate the impact of TPACK on professional adaptability. A sample of 457 junior and senior high school teachers in Indonesia and Malaysia completed the technological pedagogical and content knowledge scale and the career adaptability scale. Based on partial least square analysis, this study found that TPACK played a role in predicting four dimensions of career adaptability: concern, control, curiosity, and confidence. This structural model was also supported with path analysis. Therefore, TPACK becomes an essential aspect in influencing teachers' career adaptability.